2021
DOI: 10.3847/1538-4357/abfb6a
|View full text |Cite
|
Sign up to set email alerts
|

High Spatial Resolution Observations of Molecular Lines toward the Protoplanetary Disk around TW Hya with ALMA

Abstract: We present molecular line observations of 13 CO and C 18 O J = 3 − 2, CN N = 3 − 2, and CS J = 7 − 6 lines in the protoplanetary disk around TW Hya at a high spatial resolution of ∼ 9 au (angular resolution of 0.15"), using the Atacama Large Millimeter/Submillimeter Array. A possible gas gap is found in the deprojected radial intensity profile of the integrated C 18 O line around a disk radius of ∼ 58 au, slightly beyond the location of the au-scale dust clump at

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 53 publications
3
18
0
Order By: Relevance
“…In C 18 O emission, Fedele et al (2017) found evidence for a cavity inside 𝑟 ≈ 50 au and used DALI to infer (Müller et al 2018;Keppler et al 2018;Wang et al 2020). (6) Gas surface density at the planet's location, as inferred from C 18 O emission (Nomura et al 2021;Zhang et al 2021;Favre et al 2019;Fedele et al 2017;Isella et al 2016;Facchini et al 2021). The quoted ranges on Σ gas in AS 209, IM Lup, HD 163296, and TW Hya accommodate the possibility that the CO:H 2 abundance ratio in these discs is lower than in the ISM (Zhang et al 2019;Calahan et al 2021;Zhang et al 2021).…”
Section: Gas Surface Density: Hd 169142mentioning
confidence: 99%
See 4 more Smart Citations
“…In C 18 O emission, Fedele et al (2017) found evidence for a cavity inside 𝑟 ≈ 50 au and used DALI to infer (Müller et al 2018;Keppler et al 2018;Wang et al 2020). (6) Gas surface density at the planet's location, as inferred from C 18 O emission (Nomura et al 2021;Zhang et al 2021;Favre et al 2019;Fedele et al 2017;Isella et al 2016;Facchini et al 2021). The quoted ranges on Σ gas in AS 209, IM Lup, HD 163296, and TW Hya accommodate the possibility that the CO:H 2 abundance ratio in these discs is lower than in the ISM (Zhang et al 2019;Calahan et al 2021;Zhang et al 2021).…”
Section: Gas Surface Density: Hd 169142mentioning
confidence: 99%
“…(7) Dust surface density at the planet's location (Huang et al 2018;Nomura et al 2021;Fedele et al 2017;Benisty et al 2021) Σ gas ≈ 0.1 − 0.2 g/cm 2 near the cavity outer edge (their figure 5, top left panel, blue curve). Midplane gas temperatures according to the same thermo-chemical model (figure 5, bottom center panel) are ∼30 − 40 K, higher than the CO freeze-out temperature of ∼20 K. CO may still be depleted for other reasons (Schwarz et al 2018) but without a model we cannot quantify the uncertainty.…”
Section: Gas Surface Density: Hd 169142mentioning
confidence: 99%
See 3 more Smart Citations